Serum 25-OH vitamin D and insulin resistance in women with polycystic ovary syndrome - Ansari, Arshi; Chandra, Savita (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: This was a prospective case control study conducted in the department of obstetrics and gynecology, Era’s Lucknow Medical College and Hospital from November 2018 to March 2020. Aim was to find whether there was a link between serum 25-OH vitamin D levels, and insulin resistance in women with polycystic ovarian syndrome (PCOS). Methods: 30 newly diagnosed cases of PCOS and 30 women without PCOS were enrolled. Their clinical details as well as BMI and waist hip ratio were noted. The biochemical parameters which were measured included fasting glucose, fasting insulin, serum 25-OH vitamin D. The insulin resistance was calculated. Results: 50% of the PCOS had insulin resistance and also deficient /or insufficient vitamin D levels, versus 16.7% in the control group. This association was statistically highly significant with p value as 0.00016. No statistical significance was found with regard to the mean serum 25-OH vitamin D level. 53.4%, of the PCOS women had hirsutism versus 3.3% in the control group and was statistically significant, p value <0.0001. 20% of PCOS women had acne in contrast to 3.3% in the control group which was statistically significant with p value 0.0443. Conclusions: Hirsutism and acne were important clinical signs of PCOS. There was a negative correlation between insulin resistance and serum 25-OH vitamin D levels. Thus, vitamin D may be an important link in the genesis of PCOS. Larger randomised case control studies need to be done to understand PCOS.